Maternal erythrocytosis as a risk factor for small for gestational age at term in high altitude - Wilfredo Villamonte-Calanche; Marco Antonio Salazar-Zegarra; Cleto De-la-Torre-Dueñas; Alexandra Villamonte-Jerí; Adaí Vera-Luza; Milagros Hilari Bustinza-Apaza; Nuria Huanca-Huirse (Revista Brasileira de Ginecologia e Obstetrícia)
Abstract Objective To determine if maternal erythrocytosis is a risk factor for small-for-gestational age at term at 3,400-m altitude in pregnant women without intercurrent disease. Methods Analytical study of retrospective cohorts at Cusco, a city at 3,400-m altitude. Our participants were 224 and 483 pregnant women with and without exposure to maternal erythrocytosis, respectively. A logistic regression with the goodness of fit to the proposed model was also performed with the Hosmer and Lemeshow test, evaluating the small-for-gestational-age results with or without exposure to hemoglobin >14.5 g/dl. Results The incidence of small-for-gestational-age was 6.9% for this entire cohort. The maternal erythrocytosis during gestation without any maternal morbidity at 3,400-m altitude has an ORa=0.691 (p=0.271) for small-for-gestational-age at term. Inadequate prenatal control has an ORa=2.115 (p=0.016) for small-for-gestational-age compared to adequate prenatal control. Conclusion Maternal erythrocytosis in pregnant women without any morbidity is not a risk factor for small-for-gestational-age at 3,400 m-altitude.